Modernism and/or postmodernism in Ulysses - Almagro Jiménez, Manuel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1992)
James Joyce's Ulysses has been traditionally read as the great work of Modernism, characterized by its encyclopaedic, totalizing quality, while developing techniques to help create that effect. In spite of initial forebodings, the reader becomes accustomed to a certain narrative stability in the text. However, from "Sirens" onwards, the reader begins to feel that s/he is reading a different novel, different in fact with each new episode. The reflexion upon the quality of the episodes of the second half of the novel should force the reader to reconsider as well the previous episodes. In this way s/he will find evidence (such as the breakdown of the epistemological component or the equation between language and reality) which enables the reader to re-assess the novel also from the premises of postmodernism.